2020
DOI: 10.1055/a-1116-2407
|View full text |Cite
|
Sign up to set email alerts
|

Salt Appetite and its Effects on Cardiovascular Risk in Primary Aldosteronism

Abstract: First described in 1955 by Jerome W. Conn, primary aldosteronism (PA) today is well established as a relevant cause of secondary hypertension and accounts for about 5–10 % of hypertensives. The importance of considering PA is based on its deleterious target organ damage far beyond the effect of elevated blood pressure and on PA being a potentially curable form of hypertension. Aside the established contributory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…[27] Aldosterone, viewed as a hormone controlling sodium reabsorption and potassium excretion in the distal nephron, also plays essential pathogenetic roles in cardiovascular and renal injury. [27,28] This study aims to explore the impact of cooked meat with partial replacement of NaCl with KCl to improve liver damage and to evaluate the protective effects on the liver in terms of lipid metabolism, antioxidant, inflammation, and local RAS in mice, to produce ameliorated sodium-reduced cooked meat in physiological function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Aldosterone, viewed as a hormone controlling sodium reabsorption and potassium excretion in the distal nephron, also plays essential pathogenetic roles in cardiovascular and renal injury. [27,28] This study aims to explore the impact of cooked meat with partial replacement of NaCl with KCl to improve liver damage and to evaluate the protective effects on the liver in terms of lipid metabolism, antioxidant, inflammation, and local RAS in mice, to produce ameliorated sodium-reduced cooked meat in physiological function.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] Aldosterone, viewed as a hormone controlling sodium reabsorption and potassium excretion in the distal nephron, also plays essential pathogenetic roles in cardiovascular and renal injury. [ 27,28 ]…”
Section: Introductionmentioning
confidence: 99%
“…Despite their excessive sodium retention, patients with aldosteronism occasionally report salt cravings (14)(15)(16), and those with aldosterone-secreting adenomas consume the most sodium (17). Excessive salt intake is particularly problematic in aldosteronism because sodium intake predicts the severity of cardiac complications, including left ventricular hypertrophy (18)(19)(20)(21). Decreasing salt intake reduces blood pressure and may also reduce cardiovascular complications (19)(20)(21)(22)(23), but long-term behavioral recommendations to reduce dietary sodium are notoriously ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Aldosterone interferes with sodium homeostasis on multiple levels, including renal and central effects: Animal studies suggested that key neuronal structures involved in the regulation of salt appetite are the nucleus of the solitary tract in an intricate interplay with the central nucleus of the amygdala (CeA) [8][9][10]. In patients with aldosterone excess, such as primary aldosteronism (PA), salt appetite is impaired, which facilitates high dietary salt intake [11,12].…”
Section: Introductionmentioning
confidence: 99%